1999
DOI: 10.1097/00005537-199909000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Reconstruction Using Bone Morphogenetic ProteinLong‐Term Follow‐up in a Canine Model

Abstract: This study demonstrated that rhBMP-2 in a bioerodible particle carrier induced new host bone formation across critical-size mandibular defects. The newly formed bone successfully integrated with existing host bone creating a stable union capable of withstanding the forces of masticatory function in a canine. There was some evidence of early bone resorption (thinning of the cortical bone and decrease in height) in the rhBMP-2-induced bone. The rhBMP-2-induced bone stabilized by 11 months after reconstruction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 22 publications
(23 reference statements)
1
55
0
2
Order By: Relevance
“…In line with these results are the reported effects of rhBMP-2 15,31,32,98,99,103,110 and rhBMP-7 33 for mandibular bone regeneration in continuity defects. On the other hand, it should be mentioned that rhBMP-2, in the reports of Zhou et al 109 and Seto et al, 102 as well as rhBMP-7, in the paper of Ayoub et al, 17 have not always been associated with bony union.…”
Section: Bone Morphogenetic Proteinssupporting
confidence: 75%
See 1 more Smart Citation
“…In line with these results are the reported effects of rhBMP-2 15,31,32,98,99,103,110 and rhBMP-7 33 for mandibular bone regeneration in continuity defects. On the other hand, it should be mentioned that rhBMP-2, in the reports of Zhou et al 109 and Seto et al, 102 as well as rhBMP-7, in the paper of Ayoub et al, 17 have not always been associated with bony union.…”
Section: Bone Morphogenetic Proteinssupporting
confidence: 75%
“…Furthermore, in total, 15 scientific papers 15,18,29,31,32,[97][98][99][101][102][103]105,106,109,110 reporting on recombinant human bone morphogenetic protein-2 (rhBMP-2) as well as five publications 16,17,19,30,33 presenting data on recombinant human bone morphogenetic protein-7 (rhBMP-7) were eventually included in the current systematic approach. Thereby, the brief summarized studies of Kontaxis et al, 16 Abu-Serriah et al, 19 Boyne, 29,101 Busuttil Naudi et al, 30 and Toriumi et al 97 may give a good general impression of the effectiveness of rhBMPs regarding the quantity as well as quality of induced bone for the reconstruction of continuity mandibular defects (Details can be found in Addendum No.…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 99%
“…Indeed, this effect may help to explain the lack of concordance between bone formation in the gap and bone ingrowth. Other authors have reported an initial phase of bone resorption with both BMP-2 [21, 26,28] and BMP-7 (osteogenic protein-1) [6,17] and there are some data on the signaling pathways involved [ 1,10,13,14,16]. The lack of an initial resorptive phase with the lowest dose examined in the present study perhaps explains why this dose was associated with more bone ingrowth.…”
Section: Discussionmentioning
confidence: 43%
“…In addition, BMPs have been shown to restore substantial bone defects in numerous animal experiments, even in non-human primates [13][14][15][16] . It has already been shown that a segmental bone defect created in the mandibles of young monkeys was successfully regenerated by implanting rhBMP-2 permeating a poly-D, L-lacticco-glycolic acid-coated gelatin sponge (Fig.…”
Section: Bone Induction By Bmpsmentioning
confidence: 99%